PENGARUH MODEL QUANTUM TEACHING BERBASIS PENDIDIKAN KARAKTER TERHADAP KOMPETENSI PENGETAHUAN IPA SISWA KELAS V SD GUGUS DEWI SARTIKA DENPASAR TIMUR TAHUN AJARAN 2017/2018 - Ni KomangMega Lestari (Indonesian Journal Of Educational Research and Review, 2018)
This research aims to know the effect of quantum teaching model base character education towards science competency knowledge in 5th grade students of Gugus Dewi Sartika East Denpasar academic year 2017/2018. This study was an experiment with quasy experiment design using the Non-Equivalent Control Group Design. The population of this research is all 5th grade of Gugus Dewi Sartika East Denpasar amounting to 328 students. Sample were taken by random sampling technique. The sample of this research is 5th A grade in SDN  10 Kesiman amount 42 students as the experiment group and 5th B grade in SDN 3 Kesiman amount 53 student as the control group. The data were collected using the test method in the form of a standard multiple choice objective test. The data were analyzed using descriptive statistic and inferential in shape gain score from science competency knowledge. The result if data analysis obtained mean of gain skor from experiment group 16X"> =0,34 > 16X"> =0,25 control group. From the hypothesis test using t-test while at 5% significance level and df 83 obtained thitung =3,214 > ttabel=2,000. Based on these result can be concluded that quantum teaching model base character education influence of science competency knowledge of 5th grade students SD Gugus Dewi Sartika East Denpasar academic year 2017/2018.